Marriage in the coastal village: its rituals and social functions )Anthropological study in the coastal village Zagrin( - إيفا خرما (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The importance of studying "the rural wedding night" , emerged from the fact that, it was and still constituting one of the main social rituals in the marriage system. Because of its included meanings, it achieves an important social functions. Which in turn contribute in achieving the interaction and social solidarity requirements among members of the village community. The study shows a fundamental shifts in wedding traditional ceremonies since the seventies of the last century. This inevitable result was dictated by two processes of social acculturation and interactions, due to the revolution in communications and information. So, ceremonies of rural wedding , began to be, only a few hours in the "wedding hall", to fit the age of speed. Also, it was found that many of traditional cultural values had disappeared, while a new cultural patterns have appeared to coincide with the spirit of the age. As well as, the stability of some values from other cultures, which coexists along with the modern values, including the persistence of "Al-Naktah "(Al-Nakout) tradition, which reveals the originality of social solidarity mechanisms in the village until our days.